Plankton Metabolism in Coastal Waters of the Guangdong-Hong Kong-Macao Greater Bay: Regional Variance and Driving Factors - Zhang, Liangkui; Li, Gang; Xiang, Chenhui; Huang, Yadong; Fu, Xiaoming; Zheng, Chuanyang; Wang, Zheng; Ouyang, Zhiyuan; Song, Xingyu (Frontiers in Marine Science, 2022)
Metabolisms of field plankton community, including gross primary production (GPP), community respiration (CR) and net community production (NCP) usually indicate the status of the health, resource production and carbon budget of marine ecosystems. In this study, we explored the regional variance and driving forces of plankton metabolism in the coastal waters of the Guangdong-Hong Kong-Macao Greater Bay Area (GGBA), a fast-developed area with complex hydrological and environmental states. The results showed that the maximum GPP and CR occurred in estuarine plume in summer, while in winter the plankton community metabolism was more active in the Daya Bay. The GPP and CR were mostly affected by nutrient and temperature, respectively, and the surface water of the GGBA was divided into four zones, i.e., the river-runoff zone, river-plume zone, nearshore and far-offshore zones. The metabolic states varied significantly among these zones, due to the regional and seasonal variations of nutrient, temperature, turbidity, etc., which was driven by multiple factors including the Pearl River runoff, terrestrial and anthropogenic inputs, Yuedong Coastal Current and the intruded offshore seawater from the South China Sea. As a whole, the plankton metabolism of the GGBA showed a weak autotrophic state (NCP = 44.0 ± 207 mg C /m3 /d) as a sink of CO2 in summer, but a weak heterotrophic state (NCP = -34.8 ± 89.6 mg C /m3 /d) as CO2 source in winter. Moreover, the hypoxia is generally associated with the higher CR in bottom layer of the river plume and nearshore zones, indicating the attribution of plankton community respiration to occurrence of hypoxia in this area.